Motivation Of Farmers To Farming Rice at Rangdumulya Village, Pedes District, Karawang Regency - Putri Khairunisa; Mohamad Sam’un; Yeni Sari Wulandari (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to identify rice farmers' motivation levels and evaluate the relationship between needs categories based on the ERG Theory (existence, relatedness, growth) and rice farming in Rangdumulya Village, Pedes District, Karawang Regency. Methodology: A mixed-method approach was employed, combining quantitative and qualitative methods. Respondents were selected using Slovin's formula, with 42 farmers from the Karya Sentosa Farmer Group Association as the sample. Data were analyzed using interval width tests for motivation levels and Spearman Rank analysis for the relationship between ERG needs and farming. Results: (1) Farmers' motivation is categorized as high for existence and relatedness needs and very high for growth needs; (2) No significant relationship exists between existence and relatedness needs and farming. However, growth needs sub-variables, such as educational background and self-actualization, show significant relationships with farming. Findings: Growth factors are critical in supporting farmers' motivation. Novelty: This study highlights specific links between growth needs in ERG Theory and rice farming success. Originality: Offers new perspectives on applying ERG Theory to farmer motivation. Conclusions: Growth needs significantly enhance motivation and farming success. Type of Paper: Empirical Research Paper.